2014
DOI: 10.5089/9781498380423.001
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers from United States Monetary Policy on Emerging Markets: Different This Time?

Abstract: The impact of monetary policy in large advanced countries on emerging market economiesdubbed spillovers-is hotly debated in global and national policy circles. When the U.S. resorted to unconventional monetary policy, spillovers on asset prices and capital flows were significant, though remained smaller in countries with better fundamentals. This was not because monetary policy shocks changed (in size, sign or impact on stance). In fact, the traditional signaling channel of monetary policy continued to play th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 13 publications
2
107
1
4
Order By: Relevance
“…While employing a variety of empirical approaches, a common finding that emerges from these studies is that the unconventional policy measures employed by the FOMC since the end of 2008 have led to a significant reduction in Treasury yields and that this broad-based reduction in longer-term interest rates has been passed fully to lower borrowing costs for businesses and households. 4 To gauge the impact of LSAPs beyond US borders, Neely (2015) employs an event-style methodology and finds that these unconventional policy actions substantially lowered the foreign exchange value of the US dollar and reduced longer-term yields yields for a small sample of advanced foreign economies; Chen et al (2014) report similar results for emerging market economies. In a followup paper, Bauer and Neely (2014) use dynamic term structure models to parse out the extent to which the declines in foreign interest rates occurred through the signaling or portfolio rebalancing channels and find evidence that both channels were in operation.…”
Section: Consistent With This Predictionmentioning
confidence: 53%
“…While employing a variety of empirical approaches, a common finding that emerges from these studies is that the unconventional policy measures employed by the FOMC since the end of 2008 have led to a significant reduction in Treasury yields and that this broad-based reduction in longer-term interest rates has been passed fully to lower borrowing costs for businesses and households. 4 To gauge the impact of LSAPs beyond US borders, Neely (2015) employs an event-style methodology and finds that these unconventional policy actions substantially lowered the foreign exchange value of the US dollar and reduced longer-term yields yields for a small sample of advanced foreign economies; Chen et al (2014) report similar results for emerging market economies. In a followup paper, Bauer and Neely (2014) use dynamic term structure models to parse out the extent to which the declines in foreign interest rates occurred through the signaling or portfolio rebalancing channels and find evidence that both channels were in operation.…”
Section: Consistent With This Predictionmentioning
confidence: 53%
“…Belke and Gros provided evidence that the ECB followed the Fed in their interest rate decisions [4]. Fratzcher et al [5], Chen, et al, [6] and Tillman [7] examine the effect of changes in the US Fed Funds Rate and the US quantitative and qualitative easing to EMEs. Hofmann and Takáts show that US monetary policy affects policy, short-term and long term interest rates in EMEs and small advanced economies [8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, market reactions during the taper talk period were less evident in economies with stronger fundamentals, deeper financial markets, and better growth prospects. In another study, Chen, Mancini-Griffoli, and Sahay (2014) likewise employed event study techniques covering January 2000 to March 2014 and found that economies with stronger fundamentals were affected less by the US monetary policy shocks. Similarly, Mishra et al (2014) analyzed market reactions to the US monetary policy using event analysis and underlined the importance of macroeconomic fundamentals in easing market pressures, particularly on exchange rates and government bond yields but not on stock markets.…”
Section: IImentioning
confidence: 99%
“…The body of research is even more limited for the spillover impact of such policies on emerging markets (Chen et al 2012), but QE, which amounted to an unprecedented expansion of the US Federal Reserve balance sheet, has ignited interest in this line of research and has given rise to a growing body of literature on the impact and effectiveness of advanced economy central bank balance sheet policies (Chen, Mancini-Griffoli, and Sahay 2014). While those policies are geared toward domestic objectives such as safeguarding financial stability, supporting growth, or preventing deflation, they can nevertheless have significant spillover effects in other economies.…”
Section: Introductionmentioning
confidence: 99%